Paracoccidioides brasiliensis e Paracoccidioides lutzii, um caso secreto de amor - Arantes, Thales Domingos [UNESP] (2015)
To commemorate Prof. Carlos da Silva Lacaz’s centennial anniversary, the authors have written a brief account of a few, out of hundreds, biological, ecological, molecular and phylogenetic studies that led to the arrival of Paracoccidioides lutzii, hidden for more than a century within Paracoccidioides brasiliensis. Lacaz’s permanent interest in this fungus, and particularly his conviction on the benefits that research on paracoccidioidomycosis would bring to patients, were pivotal in the development of the field.